Hubungan Karakteristik Perawat dan Karakteristik Organisasi dengan Perilaku Caring Perawat Pelaksana di Ruang Rawat Inap Rumah Sakit Kartika Husada Pontianak 2017 - Yanti, Sri Ari; Hadi, Muhammad; Arofiati, Fitri (Jurusan Keperawatan FIKES UNSOED, 2017)
Caring behavior is an essential component of hospitalÃ¢â‚¬â„¢s quality of service. The patient satisfactionÃ¢â‚¬â„¢s survey shows the lack of caring behaviorÃ‚Â of associate nurses in Kartika HusadaÂ hospital.Ã‚Â TheÃ‚Â purposeÃ‚Â ofÃ‚Â thisÃ‚Â studyÃ‚Â wasÃ‚Â toÃ‚Â identifyÃ‚Â caringÃ‚Â behaviorÃ‚Â andÃ‚Â its associated factors in Kartika Husada hospital, Pontianak. This study was a cross sectional study.Ã‚Â TheÃ‚Â dataÃ‚Â wereÃ‚Â collectedÃ‚Â throughÃ‚Â self administered questionnaire inÃ‚Â 104Ã‚Â nurses from April to June.Ã‚Â DataÃ‚Â wasÃ‚Â analyzedÃ‚Â usingÃ‚Â univariate,Ã‚Â bivariate,Ã‚Â andÃ‚Â multivariateÃ‚Â analysis (multipleÃ‚Â logisticÃ‚Â regression).Ã‚Â TheÃ‚Â resultÃ‚Â ofÃ‚Â theÃ‚Â studyÃ‚Â showsÃ‚Â thereÃ‚Â wasÃ‚Â aÃ‚Â significant relationshipÃ‚Â betweenÃ‚Â communicationÃ‚Â patternÃ‚Â withÃ‚Â caringÃ‚Â behaviorÃ‚Â ofÃ‚Â nurses at Kartika HusadaÃ‚Â hospital,Ã‚Â Pontianak.Ã‚Â ThisÃ‚Â studyÃ‚Â suggestsÃ‚Â thatÃ‚Â nurseÃ‚Â managerÃ‚Â shouldÃ‚Â beÃ‚Â aÃ‚Â good mediator to improve caring behavior of nurses.